The orb-weaving spider genus Chrysometa in Uruguay: distribution and description of a new species (Araneae, Tetragnathidae) - Simó, Miguel; Álvarez, Luis; Laborda, Álvaro (Zootaxa, 2016)
The spider genus Chrysometa Simon, 1895 comprises 138 species of small (3–5 mm) Neotropical orb-weavers spiders (Nogueira et al. 2011; World Spider Catalogue 2015) mainly associated with arboreal vegetation from intermediate to low altitude forests (Levi 1986). Males of Chrysometa differ from other tetragnathids by having the palpal tibial length approximately as long as its widest point; paracymbium articulated and with several apophyses located at both ends; male cephalic region narrower than in the female and having cymbial ectobasal and ectomedian processes. Females are diagnosed by having femora without trichobothria; abdomen covered with silver guanine patches; a flat epigynum and also by their fertilization ducts originating anteriorly and crossing over the spermathecae (Levi 1986; Alvarez-Padilla & Hormiga 2011).